Composition chimique et qualite proteique des tourteaux de graines de coton de la Tanzanie - Jagadi, M.M.; Rundgren, M.; Ogle, R.B. (1987)
Determines the effects of area of origin and processing method on the chemical composition and protein quality of Tanzanian cottonseed expeller cakes.